Analisis Pengaruh Hubungan Suhu Cahaya Matahari Terhadap Tegangan Listrik Dan Tekanan Gas Yang Dihasilkan Pada Prototype Stasiun Pengisian Gas Hidrogen Untuk Kendaraan Fuel Cell - ramadan, dani; Wibisono Putra, Ananda Yhuto; Budiman, Abdul Hamid (Manutech : Jurnal Teknologi Manufaktur, 2024)
Efforts to create vehicles that have high efficiency and do not produce polluting exhaust gases have become the subject of research that is increasingly being developed by various automotive industry companies. Coupled with the issue of climate change which has ultimately prompted various vehicle innovations to immediately reduce the use of petroleum fuel, making various advances in the automotive sector to find substitutes for fuel to drive engines such as electricity, hybrid systems, and most recently the use of fuel cells. The research was carried out at the Tangerang Science and Technology Research Center (Puspiptek) with the aim of analyzing, studying and designing a gas refueling system (hydrogen gas refueling station). The data collection technique was carried out using an experimental descriptive method by testing the variable temperature of sunlight on the electrical voltage produced. The research results show that the hydrogen gas filling system station has a more practical filling system for filling fuel for fuel cell vehicles compared to hydrogen cylinders in general. The relationship between the temperature variables of sunlight is directly proportional to the increase in electrical voltage in the battery. Variable sunlight temperature and electrical voltage influence the increase in pressure of the gas produced. However, the gas pressure storage system has been set so as not to exceed the maximum capacity. However, vehicle systems that use fuel cells to transmit power to the engine only emit water as the end result of the combustion process. Of course, with exhaust emissions that are only water, this will make a vehicle powered by hydrogen an environmentally friendly vehicle. Even though the application in the world automotive market of vehicles with fuel cells is still limited, further developments in vehicles with fuel cells will create updated solutions in reducing the high use of petroleum as a save the earth movement on the issue of climate change.